Comparative study of endophytic bacterial strains from non-host crops for enhancing plant growth and managing early blight in tomato - Aditya Kukreti; Aditya Kukreti; Chethana Bangi Siddabasappa; Prasannakumar Muthakapalli Krishnareddy; Pramesh Devanna; Yashavanth Basavapatna Subbanna; Manjunatha Channappa; Namburi Karunakar Reddy; Abeer Hashem; Mashail Fahad Alsayed; Elsayed Fathi Abd_Allah (Frontiers in Microbiology)
Bacillus pseudomycoides, Paenibacillus polymyxa, and B. velezensis are potent bacterial endophytes, which typically exhibit host-specific interactions. However, comparative studies of these endophytes in vitro and in planta in non-host crops are lacking. Therefore, in this study, we evaluated the potential of endophytes B. pseudomycoides strain HP3d, P. polymyxa strain PGSS1, B. velezensis strain A6, and P42, isolated from various crop ecosystems in promoting plant growth and inducing systemic resistance against early blight disease in tomato. In vitro, endophytes exhibited 44.44–55.56% and 37.50–87.50% inhibition of Alternaria solani in dual culture and volatilome bioassay, respectively. In the glasshouse, individual and combined applications via seed treatment (ST), seedling dip (SD), and foliar spray (FS) significantly enhanced shoot growth (23.63–57.61%), root growth (43.27–118.23%), number of leaves (77.52–93.58%), number of shoots (33.42–45.28%) and root dry matter (42.17–43.86%), reducing early blight (PDI) by 70.95–76.12% compared to uninoculated control. Enzymatic activities, including such as polyphenol oxidase (30–40 fold), peroxidase (65.00–75.00 fold), superoxide dismutase (34.20–37.20 fold) and phenylalanine ammonia-lyase (44.44–45.56 fold) were elevated post-inoculation in endophytes treated tomato plants challenged with A. solani compared to control treated only with A. solani and declined after the fifth day. The total chlorophyll content declined from the 0th to the 10th day, but endophyte treated plants exhibited lesser reductions (2.03–2.09) than uninoculated control. Field trials confirmed the glasshouse findings, showing reduced early blight and improved growth parameters in tomato where the ST + SD + FS combination emerged as the most effective treatment for all endophytes showing 1.06–1.88 fold increase in fruit yield per plant and 28.92–32.52% decrease in PDI compared to untreated control. Thus, the study highlights the broad-spectrum potential of these strains in promoting plant growth and controlling early blight in tomato, demonstrating non-host specificity. These endophytes offer eco-friendly alternatives to chemical pesticides, supporting sustainable agriculture. Their success in field trials suggests the potential for commercialization and large-scale use across diverse crops and pave the way for further interdisciplinary research to optimize their application in integrated pest management strategies.